PENGARUH KEPEMILIKAN INSTITUSIONAL DAN PENGUNGKAPAN SUKARELA TERHADAP BIAYA HUTANG - Agustami, Silviana; Cahyani Yunanda, Anggun (Jurnal Riset Akuntansi dan Keuangan, 2014)
This research aims to find out about the effect of institutional ownership and voluntary disclosure of the interest expense on the companies manufacturing metal processing listed in Indonesia Stock Exchange. The samples used were as many as 10 metal processing manufacturing company for three years from 2010 to 2012 with a total of 30 samples by purposive sampling method. In this research, researchers used a documentary study conducted by collecting secondary data with web browsing. Voluntary disclosure is measured by scoring method on voluntary disclosure criteria that have been set. Data analysis was performed with the classical assumption and hypothesis testing with simple linear regression method. The test results show that institutional ownership is proven negative effect on the cost payable by 32% and voluntary disclosure does not have a negative effect on the cost payable.